Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Differential effects of conventional and biodegradable microplastics on carbon and nitrogen transformation and greenhouse gas emissions in Cd-contaminated riparian sediments: Responses of microbial community structure - Haojie Chen; Danlian Huang; Wei Zhou; Yang Lei; Hai Huang; Lingshi Yin; Ruihao Xiao; Rui Deng; Guangfu Wang; Wenbo Xu (Water Research, 2026)

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

Beyond the surface: how dissolved organic matter recasts the biogeochemical behaviors of micro- and nanoplastics in aquatic environments - Haojie Chen; Danlian Huang; Ruihao Xiao; Wei Zhou; Lingshi Yin; Rui Deng; Hai Huang; Yang Lei; Ruijin Li (Gondwana Research, 2026)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Let-7b-TLR7 Signaling Axis Contributes to the Anesthesia/Surgery-Induced Cognitive Impairment - Liyun Deng; Rui Gao; Hai Chen; Bo Jiao; Changteng Zhang; Liuxing Wei; Caiyi Yan; Shixin Ye-Lehmann; Tao Zhu; Chan Chen (Molecular Neurobiology, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Bioactive icetexane and abietane diterpenes from Isodon phyllopodus - Rui Deng; Juan Zou; Chen-Liang Zhao; Ye-Meng Yang; Chuen Fai Ku; Yu Zhu; Zheng-Ming Liang; Jiang-Hai Ye; Lu-Tai Pan; Hong-Jie Zhang (Natural Product Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Mechanism of Adipose-Derived Mesenchymal Stem Cell-Derived Extracellular Vesicles Carrying miR-21-5p in Hyperoxia-Induced Lung Injury - Yunfei Wu; Zhihui Zhang; Jun Li; Hai Zhong; Rui Yuan; Zihui Deng; Xu Wu (Stem Cell Reviews and Reports, 2022)

Potential ecological and health risk assessment of different kiwifruit orchards in Qianjiang district, Chongqing city, China - Mingshu Yan; Xianglun Ding; Jiali Lei; Hai Deng; Rui Wang; Qiwei Chen; Yuanyuan Gong; Pan Dong (Environmental Science and Pollution Research, 2021)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Distribution and linkage disequilibrium analysis of polymorphisms of MC4R, LEP, H-FABP genes in the different populations of pigs, associated with economic traits in DIV2 line - Zhe Chao; Feng Wang; Chang-Yan Deng; Li-Min Wei; Rui-Ping Sun; Hai-Long Liu; Quan-Wei Liu; Xin-Li Zheng (Molecular Biology Reports, 2012)

Platinum-group minerals and tellurides from the PGE-bearing Xinjie layered intrusion in the Emeishan Large Igneous Province, SW China - Wei-Guang Zhu; Hong Zhong; Rui-Zhong Hu; Bing-Guang Liu; De-Feng He; Xie-Yan Song; Hai-Lin Deng (Mineralogy and Petrology, 2010)